2011
DOI: 10.1007/s11832-011-0343-5
|View full text |Cite
|
Sign up to set email alerts
|

Elastic stable intramedullary nailing of tibial shaft fractures in children

Abstract: Purpose Tibial fractures in the skeletally immature patient are usually treated without surgery. Elastic stable intramedullary nailing (ESIN) is commonly used for other diaphyseal fracture locations. Its advantages are minimally invasive surgery with a short hospitalisation duration, primary bone union and early weight bearing. The purpose of this study was to assess the use of ESIN in displaced tibial fractures in children over 6 years old and in cases of polytrauma. Methods This study was carried out over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 21 publications
1
61
0
1
Order By: Relevance
“…[2] The use of ESIN in the proximal and distal tibia is technically demanding [3] and not free of complications. Only few reports about its application in the distal tibial metaphyseal fracture were found.…”
Section: Discussionmentioning
confidence: 99%
“…[2] The use of ESIN in the proximal and distal tibia is technically demanding [3] and not free of complications. Only few reports about its application in the distal tibial metaphyseal fracture were found.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple recently published reports have advocated early surgical stabilization of closed pediatric tibial fractures [2,3,5,9], citing instability of the fracture pattern, polytrauma, and failure to achieve or maintain reduction in a cast as indications. Despite this recommendation, we found no published reports directly comparing the outcomes of cast immobilization for closed pediatric tibial fractures with those of surgical stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been the authors' experience that older children with a closed tibial shaft fracture can be prone to delayed union and incomplete healing, which may lead to prolonged restrictions from activities and sports. Whereas flexible nail fixation has increased in popularity for the treatment of these fractures [2][3][4][5], significant complications such as compartment syndrome, malunion, nonunion, and nail migration have been reported [6,7], and casting currently remains the mainstay of treatment at most institutions [8]. The purpose of this study was to analyze success and failure of cast treatment for closed tibial diaphyseal fractures in the adolescent population.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have described irritation at the nail entry site as the most common complication following the use of titanium elastic nails, ranging in incidence from 7 to 40% , delayed healing or nonunion were described 14, 32 . Griffet J et al 31 included 86 children in his study and after 2 years of follow-up, he found the superiority of the ESIN technique over other fixation techniques, such as locking compression plate and percutaneous plating, in terms of postoperative complications. Volpon JB et al 32 concluded that the end caps inserted into the nail extremity contributed to an increase in the construct stability for torsion and axial-bending forces but not for 4-point bending forces.…”
mentioning
confidence: 94%